PENGUATAN KEMANDIRIAN HAKIM DALAM MENGEMBAN HUKUM PRAKTIS YANG PROGRESIF DI PENGADILAN NEGERI DONGGALA: (Dari Paradigma Hukum Positivisme Menuju Paradigma Hukum Progresif) - akbar, muhammad (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2020)
Freedom and independence of a judge in the birth / creating a progressive decision, is still far from expectations. This is due to size / indicators that should be owned by a judge, such as: independence, integrity and moral ethics, transparency and accountability; supervision / control (internal and external); intellect and professionalism, and impartiality, as well as faith is not maximized. The culture of law seeking justice community can not afford to support the efforts of judges in giving birth to a progressive decision. This is due to the legal culture of society in Indonesia is still low, in the sense that there is a tendency people have poor legal awareness.